How to solve this??
Attachments:
![](https://hi-static.z-dn.net/files/db9/206bc937a24f6945821d01d1024f46c9.jpg)
Answers
Answered by
1
log9 x + log9 (x-8) =1 using a couple of log properties, we have
log9 [ (x)(x - 8) ] = log9 9 so we have
(x)(x - 8) = 9 simplify
x^2 - 8x - 9 = 0 factoor
(x - 9) (x + 1) = 0 and setting each factor to 0, we have x = 9 and x = -1 .. reject the negative answer..
So, therefore x = 9...
Hope this helps you
Thanks
Mark it as brainliest
Similar questions
Math,
4 months ago
Science,
4 months ago
Math,
4 months ago
Social Sciences,
10 months ago
Accountancy,
10 months ago